Effects of High Pressure Treatment on the Hardness and Electrical Resistivity of CuW Alloy - Ma, Yu-Quan; Liu, Rong-Chang; Ma, Ji-Wei (Recent Patents on Materials Science, 2014)
The hardness and electrical resistivity of CuW alloy before and after high pressure heat treatment were tested, its microstructure was also analyzed by metallurgical microscope, scanning electron microscope and transmission electron microscopy, and the effect of high pressure treatment on hardness and electrical resistivity properties of CuW alloy was discussed. It showed that high pressure could increase hardness and room-temperature electrical resistivity of CuW alloy, which was 155HB and 3.5974x10-6 Ω.cm after 1 GPa pressure heat treatment at 900°C lasting for 20 minutes respectively, increasing by 27.05% and 6.30% as against the infiltrated CuW alloy. But the variation of the hardness and roomtemperature electrical resistivity is not obvious with increasing pressure in the range of 1-6GPa. It is mainly because the high pressure heat treatment can increase the compactness and internal dislocation density of CuW alloy. The paper is based on the following patents: US20140093420 (2014), US20130142687 (2013), CN2012102773462 (2012), CN2012102127627 (2012), CN2008101307419 (2008), CN2012102168235 (2012), CN2010101914739 (2010), CN2012102660717 (2012).
Keywords: CuW alloy